Porous nitrogen rich cadmium-tetrazolate based metal organic framework (MOF) for H-2 and CO2 uptake - Pachfule, Pradip; Banerjee, Rahul (Crystal Growth & Design, 2011)
The highly porous nitrogen rich metal organic framework [Cd-3(4-TP)(6)] (Cd-4TP-1) was synthesized solvothermally from the predesigned organic building block 4-tetrazole pyridine (4-TP) and Cd(II) as metal center using DMF as solvent. Cd-4TP-1 has a three-dimensional porous architecture where all the binding sites of Cd(II) are exclusively occupied by the nitrogen atoms from the mu(2)-tetrazolyl group or the pyridyl functionality of the 4-TP ligands. Cd-4TP-1 has Brunauer-Emmett-Teller (BET) and Langmuir surface areas of 472.2 and 728.6 m(2)/g, respectively, and shows 1.1 wt % H-2 (77 K) and 2.7 mmol/g CO2 uptake (273 K).